Spontaneous pneumoperitoneum in the course of appendicular peritonitis - Perdomo, Roberto (Cirugía del Uruguay, 2020)
A report is made of a case of spontaneous pneumoperitoneum with roentgenographic evidence, in the eourse of a gangrenous appe1;dicitis with diffuse peritonitis in a 33-year old puerpera. The diagnosis and surgical technique of appendicitis in conjunction with recent puerperium, is dealt with.